PENGARUH TUGAS PERKEMBANGAN KELUARGA TERHADAP KEPUASAN PERKAWINAN IBU YANG BARU MEMILIKI ANAK PERTAMA - Rahmaita, Rahmaita; Krisnatuti, Diah; Yuliati, Lilik Noor (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
This study aimed to analyze the influence of family characteristics and family developmental tasks on marital satisfaction of first-time mothers. This was a cross-sectional study involving 120 first-time mothers with a child aged less than two years old. Data were analyzed using multiple linear regression. The average scores of the overall family developmental task were 67,30, indicating that the developmental task of the family has been adequately fulfilled. The results showed that the increase in a family per capita income and age of the father, the better the developmental task, specifically on parents dimension. Meanwhile, a family with older mother and father was associated with a higher score of child dimension of the family developmental task. Moreover, the increase in mother's education level, the longer the marriage duration, and the higher score of the family developmental task (on both parents and child dimensions), were associated with higher marital satisfaction. Marital satisfaction was influenced by the developmental task of the family. This research reaffirms the need for families to be able to fulfill their developmental task in accordance with their developmental stages.